Social intelligence and peculiarities of managerial decision-making by higher education students studying in the speciality “Law Enforcement” - S. V. Kharchenko; O. V. Koldashov (Bulletin of Kharkiv National University of Internal Affairs)
It is emphasised that the developed social intelligence is an important property of the subject of managerial activity, which allows building more effective interpersonal relationships in terms of achieving the goal, including vertical ones: manager-subordinate.